THE INFLUENCE OF PEDAGOGICAL COMPETENCE AND ORGANIZATIONAL CULTURE ON CREATIVITY AND ITS IMPLICATIONS FOR THE PERFORMANCE OF ELEMENTARY SCHOOL TEACHERS IN LABUAN SUBDISTRICT, PANDEGLANG REGENCY - Asiah, Siti; Rustandi, Tata; Permana, Angrian (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This research is motivated by findings regarding the still low pedagogical competence, organizational culture, creativity, and performance of teachers in Public Elementary Schools in Labuan District, Pandeglang Regency. This study aims to analyze the influence of pedagogical competence, organizational culture, and creativity on teacher performance. The research method used is quantitative with a population of 91 civil servant teachers who also served as samples. The research instrument was a questionnaire using a Likert scale, while the data analysis technique used regression with the help of Smart PLS. The results of the study indicate that pedagogical competence has a positive and significant effect on teaching creativity and teacher performance. Organizational culture was also shown to have a positive and significant effect on teaching creativity and teacher performance. Furthermore, teaching creativity acts as a mediating variable, strengthening the influence of pedagogical competence and organizational culture on teacher performance. In conclusion, the better pedagogical competence, teaching creativity, and organizational culture, the more teacher performance will improve.